Development of an Antigen-DNAzyme Based Probe for a Direct Antibody-Antigen Assay Using the Intrinsic DNAzyme Activity of a Daunomycin Aptamer - Omar, Noorsharmimi; Loh, Qiuting; Gee, Jun Tye; Yee, Siew Choong; Noordin, Rahmah; Jörn, Glökler; Lim, Theam Soon (MDPI, 2014)
G-Quadruplex (G-4) structures are formed when G-rich DNA sequences fold into intra- or intermolecular four-stranded structures in the presence of metal ions. G-4-hemin complexes are often effective peroxidase-mimicking DNAzymes that are applied in many detection systems. This work reports the application of a G-rich daunomycin-specific aptamer for the development of an antibody-antigen detection assay. We investigated the ability of the daunomycin aptamer to efficiently catalyze the hemin-dependent peroxidase activity independent of daunomycin. A reporter probe consisting of biotinylated antigen and daunomycin aptamer coupled to streptavidin gold nanoparticles was successfully used to generate a colorimetric readout. In conclusion, the daunomycin aptamer can function as a robust alternative DNAzyme for the development of colorimetric assays.